Improving Employee Performance in the Laser Cutting Industry through Talent Management, Innovation Work Behavior, and Work Discipline - Sumartik Sumartik; Herlinda Maya Kumala Sari; Mochamad Rizal Yulianto (www.amertainstitute.com, 2025)
The laser cutting company provides precise, efficient and flexible material cutting solutions for various industries. The purpose of this study is to determine the effect of talent management, innovation work behavior and work discipline on employee performance in terms of developing and retaining potential employees. The research method used is quantitative research with an explanatory research approach. The population is all employees of the laser cutting company, totaling 86 employees, the sample was taken as a saturated sample. The questionnaire was distributed to respondents and analyzed using SEM PLS software with inner and outer models. The results of the study indicate that training employees with competency development and the use of the latest technology can improve employee performance. Employees are always looking for the best way to improve cutting efficiency, reduce waste and shorten machine set-up time. Compliance with working hours and work safety standards can improve employee performance. The contribution of this study strengthens the theory of resource Base View, Talent Management Framework and componential theory of creativity and innovation which practically facilitates the laser cutting industry in improving optimal work performance.